Study of the Pre-primary Stage at Mrinalini Ananda Pathsala, Gurudev’s Ashram Vidyalaya, Santiniketan — A Holistic Approach - Banerjee, Sarmila (THE PRIMARY TEACHER, 2016)
This article presents the opinion of pre-school and assistant teachers on the importance of curriculum followed at the pre-primary stage of education in Mrinalini Ananda Pathsala, Gurudev’s Ashram Vidyalaya, Santiniketan. It highlights the importance of activities followed for children so as to enable them to express their artistic creativity within modern curriculums. It also presents an empirical study that examines the opinions of pre-school and assistant teachers on the importance of educational fields, art genres and extra-curricular activities followed in the school. The pre-school teachers find each educational field, art genre and visual art activity to be of importance. Therefore, education in kindergarten has to achieve requisite holism. The paper presented is a case study. It has been found that importance is attributed to play, nature observation, learning of healthy habits, art, numeracy, movement and language, followed by rhymes, songs, dance, play and storytelling. Importance is also attributed to visual arts, i.e., drawing, craft and clay modeling. Audio-visual activities are also organised like children movies are shown to the students. Besides, the children are made to participate in jugglery, picture and other activities. Within visual arts, drawing and colouring are considered to be the most important, followed by craftwork and clay modeling. These findings can support future studies and deliberation on the possible effects on practice in terms of requisitely holistically planned pre-school education, which is the requirement for future studies.